2020
DOI: 10.1002/mds.28089
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulated Brain Cholesterol Metabolism Is Linked to Neuroinflammation in Huntington's Disease

Abstract: Huntington's disease is an autosomal‐dominant, neurodegenerative disorder caused by a CAG repeat expansion in exon‐1 of the huntingtin gene. Alterations in cholesterol metabolism and distribution have been reported in Huntington's disease, including abnormal interactions between mutant huntingtin and sterol regulatory element‐binding proteins, decreased levels of apolipoprotein E/cholesterol/low‐density lipoprotein receptor complexes, and alterations in the synthesis of ATP‐binding cassette transporter A1. Pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 183 publications
1
23
0
Order By: Relevance
“…It has been speculated that this loss underlies neuronal dysfunctions and the cognitive deficits present at this stage of life [ 41 , 42 , 43 ]. It has also been surmised that dysregulation of cholesterol metabolism is a major factor in neurological diseases accompanied by cognitive dysfunction, such as Alzheimer disease [ 44 , 45 ] (reviewed in [ 23 ]), Parkinson disease [ 46 ], and Huntington disease [ 47 ]. Epidemiological studies have suggested that individuals treated with statins have a lower risk of developing Alzheimer disease [ 25 , 28 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been speculated that this loss underlies neuronal dysfunctions and the cognitive deficits present at this stage of life [ 41 , 42 , 43 ]. It has also been surmised that dysregulation of cholesterol metabolism is a major factor in neurological diseases accompanied by cognitive dysfunction, such as Alzheimer disease [ 44 , 45 ] (reviewed in [ 23 ]), Parkinson disease [ 46 ], and Huntington disease [ 47 ]. Epidemiological studies have suggested that individuals treated with statins have a lower risk of developing Alzheimer disease [ 25 , 28 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…57 Cholesterol homeostasis and neuroinflammatory signaling are connected in neurodegeneration. 179 Indeed, Npc1 −/− mice displayed dysregulated expression of inflammatory mediators. 180 Hypercholesterolemia produces microglial activation, and high-cholesterol diet promotes inflammatory responses.…”
Section: Cholesterol In Neuroinflammationmentioning
confidence: 99%
“…Cholesterol homeostasis and neuroinflammatory signaling are connected in neurodegeneration 179 . Indeed, Npc1 −/− mice displayed dysregulated expression of inflammatory mediators 180 .…”
Section: Cholesterol In Pdmentioning
confidence: 99%
“…Their main functions include supporting, nourishing, and creating a suitable microenvironment for neuron survival ( Sofroniew and Vinters, 2010 ; Colombo and Farina, 2016 ). When astrocytes are activated to enter a pro-inflammatory state ( Sofroniew, 2014 ), the produced pro-inflammatory factors, chemokines, reactive oxygen species, and secondary messengers work together to induce neuroinflammation, resulting in multifaceted dysfunction, including but not limited to abnormal autophagy ( Bosch and Kielian, 2015 ; Thangaraj et al, 2020 ), lipid metabolism disorders ( Gonzalez-Guevara et al, 2020 ), energy supply disorders ( Trudler et al, 2015 ), and other abnormalities of cell physiology, which ultimately destroys neurons and synaptic function. At the same time, neuroinflammation hinders cell and tissue repair and regeneration, resulting in the irreversibility of neurodegeneration ( Schain and Kreisl, 2017 ).…”
Section: Introductionmentioning
confidence: 99%